Choledochal Malformation in Children: Lessons Learned from a Dutch National Study - van den Eijnden, Maria. H. A. (World J Surg, 2017)
INTRODUCTION: A choledochal malformation (CM) is a rare entity, especially in the Western world. We aimed to determine the incidence of CM in the Netherlands and the outcome of surgery for CM in childhood. METHODS: All pediatric patients who underwent a surgical procedure for type I–IV CM between 1989 and 2014 were entered into the Netherlands Study group on choledochal cyst/malformation. Patients with type V CM were excluded from the present analysis. Symptoms, surgical details, short-term (<30 days) and long-term (>30 days) complications were studied retrospectively. RESULTS: Between January 1989 and December 2014, 91 pediatric patients underwent surgery for CM at a median age of 2.1 years (0.0–17.7 years). All patients underwent resection of the extrahepatic biliary tree with restoration of the continuity via Roux-en-Y hepaticojejunostomy. Twelve patients (12%) were operated laparoscopically. Short-term complications, mainly biliary leakage and cholangitis, occurred in 20 patients (22%), without significant correlations with weight or age at surgery or surgical approach. Long-term postoperative complications were mainly cholangitis (13%) and anastomotic stricture (4%). Eight patients (9%) required radiological intervention or additional surgery. Surgery before 1 year of age (OR 9.3) and laparoscopic surgery (OR 4.4) were associated with more postoperative long-term complications. We did not observe biliary malignancies during treatment or follow-up. CONCLUSION: Surgery for CM carries a significant short- and long-term morbidity. Given the low incidence, we would suggest that (laparoscopic) hepatobiliary surgery for CM should be performed in specialized pediatric surgical centers with a wide experience in laparoscopy and hepatobiliary surgery.